تحديد سلوك حجم الرتل ومعدل ضياع الرزم اعتماداً على رزم ER - حسن عباس; هيثم الرضوان; ناجي محمد (Tishreen University, 2019)
يتميز هذا البحث في حساب تابع التوزيع الاحتمالي الممثل لحجم الرتل في مجال الرشقة والرزمة. ففي هذه المقالة تم تحديد السلوك الأسي الممثل لحجم الرتل بالاعتماد على رزم زيادة المعدل. وتبيان تأثير معدل التناقص على حجم الرتل عند احتمالية أن يتجاوز حجم الرتل لقيمة محددة، فضلاً عن تأثير حجم المسجل على احتمالية الضياع لرزم VoIP وتحديد نمط غاوص ليمثل سلوكية احتمال ضياع الرزم مع زيادة حمل الحركة عند مسجل ذي حجم ثابت. This research is characterized by calculation of the fitting Probability Distribution Function for packet-scale queuing and burst-scale queuing. This paper defines the Exponential behavior of queue size depending on excess rate packets, and shows the effect of decay rate on the queue size at the probability that the queue size exceeds the defined threshold. In addition we analyze the effect of Buffer size on the probability of packet lost VoIP packets and we define the Gaussian model to represent best fitting function to probability of packet lost at increasing the load when the buffer size is constant.